Minority Politics in the Punjab - Nayar, Baldev Raj (Book collections on Project MUSE., 1966)
This full-scale study of Punjabi politics since Indian Independence in 1947 considers the major political problem confronting virtually every new nation: how to create a functioning political system in the face of divisive internal threats. Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.